Quality Evaluation of Different Brands of Telmisartan Tablets in Bangladesh for Ensuring Therapeutic Reliability in Hypertension Management - Bahar , Nasiba Binte; Hossain, S M Rakibul; Tania, Nowrin Jahan; Mou, Sumiya Sharmin; Faruqui, Adeeba Jaheen; Al Mamun, Md Elias (Bangladesh Pharmaceutical Journal, 2026)
Telmisartan, an angiotensin-II receptor blocker, is widely prescribed for hypertension in Bangladesh. This study aims to compare the quality of various brands of telmisartan tablet by evaluating key quality control parameters, including weight variation, hardness, friability, thickness, diameter, disintegration time, potency and dissolution profiles. The weight variation test revealed that five brands (F1-F5) complied with the pharmacopeial ± 7.5% limit, with brand F3 being the only exception. Tablet thickness and diameter varied across brands, likely due to differences in granule density and manufacturing processes. Hardness testing showed that brand F6 had the highest average hardness, while brand F4 had the lowest. In the disintegration test, all brands met the pharmacopeial standard, with brand F4 exhibiting the fastest disintegration time. Friability testing demonstrated low friability across all brands. Dissolution profiles indicated significant differences in drug release rates. Kinetic analysis revealed that brands F1, F3 and F5 followed a diffusion-controlled release mechanism, whereas brands F2, F4 and F6 exhibited dissolution-controlled release. Potency testing confirmed that all brands fell within the acceptable potency range of 95-110%. Among all the brands, brand F4 stood out as the best, demonstrating superior performance in various parameters. Overall, the results of all these quality control parameters for the different brands were within the limits specified by pharmacopoeia. Therefore, it can be concluded that the marketed telmisartan tablets of these brands are safe, effective and efficacious, as well as compliant with the required quality control standards. Patients can, therefore, safely switch from one brand to another without compromising therapeutic efficacy. Bangladesh Pharmaceutical Journal 29(1): 134-143, 2026 (January)